Delivery of curcumin by directed self-assembled micelles enhances therapeutic treatment of non-small-cell lung cancer - Zhu WT (Dove Medical Press, 2017)
Wen-Ting Zhu,1,2,* Sheng-Yao Liu,3,* Lei Wu,1,2 Hua-Li Xu,4 Jun Wang,1,2 Guo-Xin Ni,3,5 Qing-Bing Zeng1,2 1Biomaterial Research Center, School of Pharmaceutical Sciences, Southern Medical University, Guangzhou, China; 2Guangdong Provincial Key Laboratory of New Drug Screening, School of Pharmaceutical Sciences, Southern Medical University, Guangzhou, China; 3Department of Orthopeadics and Traumatology, Nanfang Hospital, Southern Medical University, Guangzhou, China; 4Department of Anesthesiology, Zhujiang Hospital, Southern Medical University, Guangzhou, China; 5Department of Rehabilitation Medicine, First Affiliated Hospital, Fujian Medical University, Fuzhou, China *These authors contributed equally to this work Background: It has been widely reported that curcumin (CUR) exhibits anticancer activity and triggers the apoptosis of human A549 non-small-cell lung cancer (NSCLC) cells. However, its application is limited owing to its poor solubility and bioavailability. Therefore, there is an urgent need to develop a new CUR formulation with higher water solubility and better biocompatibility for clinical application in the future. Materials and methods: In this study, CUR-loaded methoxy polyethylene glycol–polylactide (CUR/mPEG–PLA) polymeric micelles were prepared by a thin-film hydration method. Their characteristics and antitumor effects were evaluated subsequently. Results: The average size of CUR/mPEG–PLA micelles was 34.9±2.1 nm with its polydispersity index (PDI) in the range of 0.067–0.168. The encapsulation efficiency and drug loading were 90.2%±0.78% and 9.1%±0.07%, respectively. CUR was constantly released from the CUR/mPEG–PLA micelles, and its cellular uptake in A549 cells was significantly increased. It was also found that CUR/mPEG–PLA micelles inhibited A549 cell proliferation, increased the cell cytotoxicity, induced G2/M stage arrest and promoted cell apoptosis. Moreover, the CUR/mPEG–PLA micelles suppressed the migration and invasion of A549 cells more obviously than free CUR. Additionally, CUR/mPEG–PLA micelles inhibited human umbilical vein endothelial cells migration, invasion and corresponding tube formation, implying the antiangiogenesis ability. Its enhanced antitumor mechanism may be related to the reduced expression of vascular endothelial growth factor, matrix metalloproteinase (MMP)-2, MMP-9 and Bcl-2 as well as the increased expression of Bax. Conclusion: The mPEG–PLA copolymer micelles can serve as an efficient carrier for CUR. The CUR/mPEG–PLA micelles have promising clinical potential in treating NSCLC. Keywords: curcumin, mPEG–PLA, polymeric micelles, A549 cells, HUVECs, angiogenesis